Quantum engineering of superconducting structures: principles, promise and problems - Zagoskin, Alexandre (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
Quantum technologies went through an explosive development since the beginning of the century. The progress in the field of superconducting quantum structures was especially fast. As the result, the design and characterization of large quantum coherent structures became an engineering problem. We will discuss the current status of the emerging discipline of quantum engineering and possible ways of meeting its main challenge, the fundamental impossibility of an efficient modelling of a quantum system using classical means.